Real Convergence in the European Union : An Empirical Analysis (2018)
Over the next couple of years, the European Union will face a difficult stage, being confronted with the eventual transition to a monetary union. In the beginning of 1997, it is less clear than ever, if and when the European Monetary Union will eventually be realized, which countries will join in this process, and which countries will benefit from monetary union or are likely to loose out. Using econometric methods, the work attempts to assess the real economic effects of the European Monetary Union. In a first step, differences in labor and goods market adjustment processes between the fifteen member states of the European Union, the United States and Canada are studied in order to evaluate the short-term prospects of monetary union. Turning to the long-run effects, within a second step, convergence of living standards is assessed.